Impact of Caspian Crude Oil on Turkish Straits - Bilen Alkan, Guler (Asian Journal of Chemistry, 2010)
The Turkish Straits, for the last 10 years at least, have turned into one of the key shipping foci of the world seaborne oil trade, such as the Suez Canal, the Strait of Malacca and the Strait of Dover. It was previously the same in 1892. In that year, oil cargoes loaded in the Black Sea port Batumi were delivered by tankers to their customers in the Far East destination(s), all passing through the Turkish Straits. Nearly 123 million tons of oil passed through the Strait of Istanbul in 2002, representing 5 per cent of the oil traded by sea. The Dumber of crude carriers that passed through the Strait for that period, up or down, was 6022. In other words, 15 crude oil carriers a day sailed through the Bosphorus, laden or in ballast. Similarly, 1330 tankers carryiDg LPG and chemicals also used the Strait, meaning 4 additional but smaller size tankers a day On top of the above figure. Shipping traffic in the Strait was 4125 transits in the year 1841 and almost tripled in 1856, during the Crimean War. There are now an average of 25.000 transits per year in each direction including, inter alia, tankers, chemicals, product tankers, LNG and LPG carriers-the largest size passing through being 150 to 160.000 tonners fully laden or vessels of around 300 m in length partly laden. Almost one-third of the total transits are the local ships passing through the Strait. This paper provides an overview of the impact of Caspian crude on Turkish Straits and also explains the geographical location of Turkish Straits and includes lines that connect to Caspian crude.